Information and education provision in bronchiectasis: co-development and evaluation of a novel patient-driven resource in a digital era. Issue 4 (12th April 2018) - Hester, Katy L.M.; Newton, Julia; Rapley, Tim; Ryan, Vicky; De Soyza, Anthony
Bronchiectasis presents a significant burden of disease for patients, their families and healthcare services, with recurrent hospital admissions and poorer health-related quality of life, in addition to higher rates of fatigue, depression and cardiovascular disease [1–3]. The increasing prevalence and burden of bronchiectasis is recognised worldwide [3–6]. Patient education is a fundamental part of long-term management planning, as highlighted in the new European Respiratory Society guidelines, yet there is a lack of information available to patients in comparison to other chronic respiratory conditions. Improvements in information for those living with bronchiectasis should use patient-driven co-development processes http://ow.ly/vWCB30iCn2M